2017
DOI: 10.14198/jhse.2017.121.05
|View full text |Cite
|
Sign up to set email alerts
|

The effects of match-playing aspects and situational variables on achieving score-box possessions in Euro 2012 Football Championship

Abstract: The aim of this study was to examine the independent and interactive effects of several match-playing aspects and situational variables on the probability of achieving score-box possessions in the 2012 European Championship. The non-clinical magnitude-based inferences method was used to interpret the true effect of the performance indicators on the response variable. The logistic regression analysis in univariate perspective showed that the probability of achieving score-box possessions was greater in the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…This training mode causes considerable improvements at the physiological level, but it needs a lot of time and it neglects the training of specific technical and tactical skills [6]. On the other hand, the technical and tactical level of proficiency seems to be discriminant factors for profiling offensive processes [7][8][9] and winning international competition [10]. Accordingly, the multiple requests of the modern game have prompted coaches and sports scientists looking for new methods and exercises, which are able to simultaneously improve physical capacities, and technical and tactical skills of the players.…”
Section: Introduction mentioning
confidence: 99%
“…This training mode causes considerable improvements at the physiological level, but it needs a lot of time and it neglects the training of specific technical and tactical skills [6]. On the other hand, the technical and tactical level of proficiency seems to be discriminant factors for profiling offensive processes [7][8][9] and winning international competition [10]. Accordingly, the multiple requests of the modern game have prompted coaches and sports scientists looking for new methods and exercises, which are able to simultaneously improve physical capacities, and technical and tactical skills of the players.…”
Section: Introduction mentioning
confidence: 99%
“…The free kick is the penalty that is awarded after a foul committed in the penalty area by the defending team to the team that committed the foul. Individually the attacker must use the shot on goal to score, the defenders need the goalkeeper and his technique and therefore a defence of the spaces in case of a post or a crossbar or the goalkeeper himself (Sgrò et al, 2017). The correlation between indicator and descriptor is tight, moreover the physical effort is maximum, that of strength is average and finally that of speed is maximum.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the data was examined using intra-rater agreement through the percentage-error method recommended by Hughes et al (2004). This method suggests that matches must be analysed twice, with a break between the two analyses to avoid any possible adverse memory and learning effects (Sgrò et al, 2017). Therefore, for the purpose of the present study, five matches were randomly selected and observed twice within a one-week period.…”
Section: Match Samplementioning
confidence: 99%